2016
DOI: 10.2507/26th.daaam.proceedings.091
|View full text |Cite
|
Sign up to set email alerts
|

The use of Fuzzy Neural Structures to Increase the Reliability of Drilling Platforms

Abstract: The use of semiconductor converters as a part of sea drilling platforms' electrical power systems is the cause of rising of electromagnetic compatibility and inactive power problems that demands an incorporation of the active filter compensation devices. It is known that in such real systems the capacitor of filter is discharging because of the existence of active power losses and it has negative impact on electric power quality. In the article, authors propose advanced ANFIS controller that allows to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Fuzzy logic has a wide range of utilizations in decision making since it condenses a large amount of parameters into smaller fuzzy sets [11].…”
Section: Fuzzy Logic Methodology For Decision Makingmentioning
confidence: 99%
“…Fuzzy logic has a wide range of utilizations in decision making since it condenses a large amount of parameters into smaller fuzzy sets [11].…”
Section: Fuzzy Logic Methodology For Decision Makingmentioning
confidence: 99%
“…possible to explain the maximum value of observed in pilot researches [5,7] On the assumption of engineering aspects of of horizontal type for process optimization of epitaxy operations and movement of a flow of the Investigational studies confirmed that separation points and flow reattachment, separating emergence of a difficult heating pattern on a substrate surface even in case of the heating system. This influence is defined b susceptor, the inflow speed of gas of outflow of gas, the character of a current of gas drainage and a level of its heating reactor [8][9].…”
Section: Influence Of Location Of Stagnation Point Of Flow and Changementioning
confidence: 99%
“…The ANFIS structure is based on an artificial neural network and consists of five layers in which the neurons have different structures and perform different functions [19]. The proposed structure is designed to respond to the analyzed problem.…”
Section: Anfismentioning
confidence: 99%